The Publishing Trap [Product Review] - Alonso Avila; Amy Chen; Heather Healy; Mahrya Carncross; Wendy C. Robertson; Willow Fuchs (Journal of Librarianship and Scholarly Communication, 2018)
Review of The Publishing Trap, created by Jane Secker and Chris Morrison. UK Copyright Literacy team, 2016. Free download. https://copyrightliteracy.org/resources/the-publishing-trap/